Integrating Strategic and Tactical Forest-Management Models within a Multicriteria Context. Issue 2 (4th December 2018) - Belavenutti, Pedro; Romero, Carlos; Diaz-Balteiro, Luis
Abstract: Forest-management planning could be addressed at various temporal scales, namely strategic and tactical scales. The former are associated with extended temporal horizons, whereas the latter focus on shorter periods of time and typically encompass further spatial requirements. On the other hand, in most forestry scenarios, the existence of multiple criteria of different nature is the rule rather than the exception. It seems sensible to think that forest-management models would significantly increase their practicality in many cases, if the strategic and tactic models were to be integrated within a multicriteria context. This paper presents an integrated framework for dealing with this type of situation. Thus, two approaches called " top down " and " integrated " have been formulated. To undertake this task, the well-known tool called extended goal programming has been resorted to. The functioning and the strengths of the integrated framework are illustrated with a case study corresponding to fast-growing plantations in Brazil. This framework includes the decisionmaker's preferences in a more compact model that allows the inclusion of different spatial issues.